Age Selectivity among Labour Migrants (Majoni Joni) From South-Eastern Zimbabwe to South Africa during a Prolonged Crisis (African Human Mobility Review, 2021)
Focusing on unskilled Zimbabweans, this paper assesses the influence of the prolonged Zimbabwean crisis (2000–2016) on age differences in migration to South Africa. It is based on a questionnaire survey conducted among 166 households in 4 south-eastern districts in 2016/2017. Three-fifths of the households had migrant members in South Africa driven by the lack of jobs, poverty or food shortages at home. Labour migration to South Africa was maledominated and involved younger people (below 30) than older people. Most of the migrants aged 30 or older moved during the peak of the crisis (2006–2010), most likely under the pressure of finding a means of survival for their families left behind. Young men who have a pre-crisis history in this migration predominated again after the crisis peak (after 2010). Most of this labour migration was clandestine and involved people with low levels of education. Hence, most of these migrants worked as ‘general hands’ earning ZAR 1,500 or less per month in South Africa. In this paper, it is argued that the Zimbabwean government should control such risky youth migration by creating jobs or income-generating projects in Zimbabwe and educating youth about unsafe migration.